Validation of a numerical model for the mechanical behavior of a continuous positive airway pressure mask. Issue 2 (3rd February 2022) - Genna, Francesco; Lopomo, Nicola Francesco; Savoldi, Fabio
Abstract: Finite Element models (FEM) are developed for the analysis of the contact pressures exerted by a Continuous Positive Airway Pressure (CPAP) mask applied to a dummy head. This is seen as a preliminary step in the analysis of the mechanical effects of CPAP masks applied to human faces, such as recently employed for the care of COVID-19 patients, or other purposes. These mechanical effects can range from negligible, in the case of correct positioning, sufficiently light tension in the headgear, correct mask design, etc., to the possible development of device-related pressure ulcers and/or dentofacial deformations, especially in children. The results of Finite Element analyses are compared, for their validation, with experimental ones. The numerical analysis tool appears able to predict, at an acceptable cost, both the intensity and the area distribution of the contact pressures, as well as the force-displacement relationship occurring in the headgear. This might help the design and the production of more effective and tolerable CPAP masks.